DESIGN OF POTTERY CRAFTSMEN’S SETTLEMENT WITH BEHAVIORAL ARCHITECTURE APPROACH (CASE STUDY: DUKUH KRAJAN, MALANG) - Dyah Kusuma Wardhani; Hari Purnomo; Happy Ratna Santosa (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2012)
The presence of pottery industry in Dukuh Krajan a potential to home-based Indus-try that can be developed in Malang. But the existence of craftmen’s settlement is not planned and managed well, so there are several problem that exist such as the lack of natural lighting and ventilation inside the house, kiln in the middle of the settlement pollutes the air and fire risk,and space conflict in craftmen house between domestic and economic needs. Behavioral architecture approach is used to make sure the design result based on the society’s needs and behavior. This is a qualitative study which is focussed on community’s social condition. Samples for this study consists of three elements, place, actors, and activity. For activity sample, data that being observed is covert behavior (collected through interviews) and overt behavior (collected through observation). The expected result is model of an alternative block plan in the pottery craftmen’s settlement. Block plan design shows the arrangement of the building mass and open space in pottery craftsmen’s settlement that can provide solutions to security and comfort of the building. Design performed on selected existing locations, existing condition and community are used as a basis for composing the design criteria.